2012
DOI: 10.1007/s00227-012-2100-9
|View full text |Cite
|
Sign up to set email alerts
|

Pluri-annual study of the reproduction of two Mediterranean Oscarella species (Porifera, Homoscleromorpha): cycle, sex-ratio, reproductive effort and phenology

Abstract: This study presents the phenology of two common Mediterranean sponges belonging to the genus Oscarella (Porifera, Homoscleromorpha). Oscarella tuberculata and Oscarella lobularis are two sibling species, dwellers of shallow benthic communities which tend to have distinct ecological behavior, respectively, euryecious and rather stenoecious. The comparative study of their reproductive cycle showed that both Oscarella species have a seasonal reproductive cycle with a successive phase duration differing from one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…This is also corroborated by the presence of diagnostic positions in both mt DNA markers for each species (Figure S3). Cell composition [12], symbiotic microbe diversity [21], as well as life history traits such as sex ratios and reproductive cycles, also differ between O. lobularis and O. tuberculata, consistent with the presence of two distinct species [14]. Concerning color polymorphism, the type species O. lobularis displays not only the classical purple/ivory color arrangement but can also be blue, pink and purple.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This is also corroborated by the presence of diagnostic positions in both mt DNA markers for each species (Figure S3). Cell composition [12], symbiotic microbe diversity [21], as well as life history traits such as sex ratios and reproductive cycles, also differ between O. lobularis and O. tuberculata, consistent with the presence of two distinct species [14]. Concerning color polymorphism, the type species O. lobularis displays not only the classical purple/ivory color arrangement but can also be blue, pink and purple.…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies have found soft specimens of Oscarella which do not have the habitual purple/ivory coloring, but which are blue, entirely purple or pink. Similarly, cartilaginous specimens of Oscarella may also be purple or pink in addition to the green, blue and yellow morphotypes [13], [14]. Subsequent, finer histological studies revealed additional differences among various color morphs of Oscarella, and the ‘cosmopolitan’ O. lobularis turns out to be different species (10 new species of Oscarella have been described during the last 20 years) [15], [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large number of specimens of H. fulva investigated, no spermatocysts were observed. A very low ratio of male: Female individuals has been reported for many marine sponges (Hogg 1967;Scalera Liaci et al 1971;Ayling 1980;Corriero et al 1996;Corriero et al 1998;Mercurio et al 2007;Ereskovsky et al 2013). For example, after 2 years of fortnightly monitoring, Ayling (1980) found males of Aaptos aaptos (SCHMIDT 1864) in only 1 year of the study.…”
Section: Reproductive Patternmentioning
confidence: 84%
“…; Ereskovsky et al. ). For example, after 2 years of fortnightly monitoring, Ayling () found males of Aaptos aaptos ( Schmidt 1864) in only 1 year of the study.…”
Section: Discussionmentioning
confidence: 97%